The first molecular study of Cystoisospora belli and Cyclospora cayetanensis in HIV/AIDS patients from Northern Iran - Bahareh Basirpour; Mitra Sadeghi; Saba Ramezanzadeh; Niloofar Daryaee; Shirzad Gholami; Seyed Abdollah Hosseini; Ehsan Ahmadpour; Ahmad Daryani; Sargis A. Aghayan (Scientific Reports)
Abstract Cystoisospora belli and Cyclospora cayetanensis have been known to cause a range of gastrointestinal and systemic complications, particularly in HIV/AIDS patients with low immunity. The manifestations are more severe in patients with CD4 + T-cell counts below 200 cells/µl. The current study was performed to detect these parasitic infections in HIV-positive patients in northern Iran. This cross-sectional study analyzed 50 stool samples from HIV-positive patients attending behavioral disease counseling centers in Mazandaran province, northern Iran. Following informed consent, the samples were tested for C. cayetanensis and C. belli using polymerase chain reaction (PCR) testing. Among 50 stool samples tested, 8% [95% CI: 0.48–15.52] (n = 4) were positive for C. belli while 4% [95% CI: 0.00–9.43] (n = 2) were positive for C. cayetanensis. Also infection with C. belli showing a significant association with gastrointestinal symptoms (p < 0.05). Moreover, 52% of patients reported gastrointestinal issues, primarily diarrhea and abdominal cramps. The majority of individuals (66%) resided in rural villages, and more than half (56%) were under 50 years old. Notably, 52% had CD4 + T-cell counts below 500 cells/mL. Detecting these pathogens highlights their continued public health significance, especially in rural populations. Notably, a significant association was observed between C. belli infection and gastrointestinal symptoms, emphasizing the need for early diagnosis and clinical vigilance. Given the burden of these infections, targeted screening and preventive strategies should be prioritized.